“Lift Off to Leadership: Elevate Your Impact by Cultivating Skills and Mindset for Working with Senior Leaders” – Reflective Highlights from EAHIL 2024 (Journal of EAHIL, 2024)
Effectively communicating and collaborating with senior leaders across an organization is an essential skillset for any library leader. This article highlights several key takeaways to consider when crafting a compelling business case or project proposal for your organizational decision-makers.